National Seminar on school buildings. Paper no.3, "educational considerations". - Manahan, Geronimo V. (Manila [publisher not identified], 1971)
Educational considerations on the selection of sites and the construction of buildings are discussed in the light of the need of first-level education, and the lower and upper section of second-level education. Accommodation of the school is closely tied with the organisation of the school curriculum and the second section of the Paper deals with problems of space wastage and how to overcome it.
Attached in this book is the program of "National Seminar on School Buildings", Manila, November 16-18, 1971. Organized by the UNESCO National Commission of the Philippines in cooperation with the ASIAN Regional Institute for School Building Research.
Keywords: School facilities -- Planning; School buildings -- Philippines; School buildings -- Philippines -- Congresses